The Effectiveness of Using Assemblr Edu Learning Media to Help Student Learning at School - Nuur Wachid Abdul Majid; Muhammad Rafli; Noviyanti Nurjannah; Putri Apriyanti; Sofyan Iskandar; Fitri Nuraeni; Hafiziani Eka Putri; Pratama Benny Herlandy; Mohamed Nor Azhari Azman (Jurnal Penelitian Pendidikan IPA, 2023)
Assemblr Edu is an application that provides interactive 3D augmented reality-based learning media for students. research was conducted on the effectiveness of the application as a learning medium for teaching and learning activities of the Assemblr Edu application. In the application, various learning topics are presented that can be studied by students from elementary to high school levelsThis research uses a descriptive quantitative research method by utilizing google Forms in disturbing questionnaires in form of questionnaires. The result of the research is: The Assemblr Edu learning application can be a more interesting and modern learning solution to be applied in schools; The use of the Assemblr Edu application which is quite easy can provide opportunities for more effective learning with the features of learning topics that are already complete enough to be learned; the lack of knowledge of students about Augmented Reality technology has an impact on the Assemblr Edu application that is rarely used by schools or students independently; and support from hardware such as smartphones is very important with specifications that are large enough in terms of memory storage, to run applications better and efficiently and connection stability also affects the use of this learning application.